A facile synthesis of ZnO/Manganese hexacyanoferrate nanocomposite modified electrode for the electrocatalytic sensing of riboflavin. (October 2018) - Selvarajan, S.; Suganthi, A.; Rajarajan, M.
Abstract: This paper demonstrates the development of an electrochemical sensor based on ZnO-manganese hexacyanoferrate nanocomposite (ZnO/MnHCNF)- modified glassy carbon electrode (GCE) for detecting riboflavin (RF) in 0.1 M PBS (pH 6.4) using voltammetric studies. The GCE was prepared by depositing appropriate amounts of ZnO on the surface of GCE, followed by depositing manganese hexacyanoferrate (MnHCNF) nanoparticles. The morphology and the interface properties of ZnO/MnHCNF composite were examined using UV–visible, FT-IR, X-ray diffraction, BET-surface area, scanning electron microscopy, energy dispersive X-ray spectroscopy, transmission electron microscopy with SAED pattern and electrochemical impedance spectroscopy. The modified electrode exhibits excellent sensing performance for detecting RF with a linear range from 0.2 to 3.0 μM and a detection limit of 0.0101 nM (S/N = 3). Under optimal conditions, the sensor displays excellent stability and satisfactory results in real samples analysis. Graphical abstract: Image 1 Highlights: A novel ZnO/MnHCNF nanocomposite was synthesized using a facile chemical precipitation method. The ZnO/MnHCNF nanocomposite shows a high electrocatalytic activity towards the oxidation of riboflavin. The ZnO/MnHCNF nanocomposite can be an effective sensor for direct determination of various real samples.